Gestión del conocimiento y su impacto en las habilidades digitales para la eficiencia y eficacia del personal administrativo de la universidad técnica estatal de Quevedo UTEQ, año 2023 - Párraga Padilla, Carmen Elizabeth (2024)
The present research project aims to evaluate the impact of knowledge management in digital skills for the efficiency and effectiveness of the administrative staff of the UTEQ, year 2023. Managers of organizations recognize that the development of human capital is decisive for the success of business activities. This implies a conscious, pragmatic, and focused orientation on processes that strengthen the digital skills that employees need in their jobs. The problem posed is How does knowledge management impact digital skills for efficiency and effectiveness in the administrative staff of UTEQ? The research is descriptive, exploratory and documentary, the methods used were deductive, inductive, analytical and descriptive, the technique applied was the survey, a questionnaire was developed with 36 questions on knowledge management and digital skills and 16 questions on efficiency and effectiveness in their job performance on a Likert scale, The instruments were validated by 5 experts, in addition a SWOT was performed to know the real situation of internal and external factors that affect the efficiency and effectiveness of the use of digital skills, the results show that there is a positive correlation between effective knowledge management and digital skills, and high levels of labor productivity Translated with DeepL.com (free version)